The atrial secondary tricuspid regurgitation is associated to more favorable outcome than the ventricular phenotype - Gavazzoni, Mara; Heilbron, Francesca; Badano, Luigi P.; Radu, Noela; Cascella, Andrea; Tomaselli, Michele; Perelli, Francesco; Caravita, Sergio; Baratto, Claudia; Parati, Gianfranco; Muraru, Denisa (Frontiers in Cardiovascular Medicine, 2022)
Aim We sought to evaluate the differences in prognosis between the atrial (A-STR) and the ventricular (V-STR) phenotypes of secondary tricuspid regurgitation. Materials and methods Consecutive patients with moderate or severe STR referred for echocardiography were enrolled. A-STR and V-STR were defined according to the last ACC/AHA guidelines criteria. The primary endpoint was the composite of all-cause death and heart failure (HF) hospitalizations. Results A total of 211 patients were enrolled. The prevalence of A-STR in our cohort was 26%. Patients with A- STR were significantly older and with lower NYHA functional class than V-STR patients. The prevalence of severe STR was similar (28% in A-STR vs. 37% in V-STR, p = 0.291). A-STR patients had smaller tenting height (TH) (10 ± 4 mm vs. 12 ± 7 mm, p = 0.023), larger end-diastolic tricuspid annulus area (9 ± 2 cm2 vs. 7 ± 6 cm2/m2, p = 0.007), smaller right ventricular (RV) end-diastolic volumes (72 ± 27 ml/m2 vs. 92 ± 38 ml/m2; p = 0.001), and better RV longitudinal function (18 ± 7 mm vs. 16 ± 6 mm; p = 0.126 for TAPSE, and −21 ± 5% vs. −18 ± 5%; p = 0.006, for RV free-wall longitudinal strain, RVFWLS) than V-STR patients. Conversely, RV ejection fraction (RVEF, 48 ± 10% vs. 46 ± 11%, p = 0.257) and maximal right atrial volumes (64 ± 38 ml/m2 vs. 55 ± 23 ml/m2, p = 0.327) were similar between the two groups. After a median follow-up of 10 months, patients with V-STR had a 2.7-fold higher risk (HR: 2.7, 95% CI 95% = 1.3–5.7) of experiencing the combined endpoint than A-STR patients. The factors related to outcomes resulted different between the two STR phenotypes: TR-severity (HR: 5.8, CI 95% = 1, 4–25, P = 0.019) in A-STR patients; TR severity (HR 2.9, 95% CI 1.4–6.3, p = 0.005), RVEF (HR: 0.97, 95% CI 0.94–0.99, p = 0.044), and RVFWLS (HR: 0.93, 95% CI 0.85–0.98, p = 0.009) in V-STR. Conclusion Almost one-third of patients referred to the echocardiography laboratory for significant STR have A-STR. A-STR patients had a lower incidence of the combined endpoint than V-STR patients. Moreover, while TR severity was the only independent factor associated to outcome in A-STR patients, TR severity and RV function were independently associated with outcome in V-STR patients.